GLOBAL STATISTICS OF BOLIDES IN THE TERRESTRIAL ATMOSPHERE - L. F. Chernogor; M. B. Shevelyov (Radio Physics and Radio Astronomy, 2017)
Purpose: Evaluation and analysis of distribution of the number of meteoroid (mini asteroid) falls as a function of glow energy, velocity, the region of maximum glow altitude, and geographic coordinates.